Kepemimpinan Kharismatik Kiai di Pondok Pesantren Ali Maksum Krapyak Yogyakarta - Rosita, Neni (SANGKéP: Jurnal Kajian Sosial Keagamaan, 2018)
Leadership is the most important foundation in a country, institutions and organizations. Leadership talks about how one can influence, inspire and make others want to learn extra work sincerely. Many say the ability of lead associated with talent, but to be sure, the leadership is a skill that needs to be trained not only studied the science and theory. Boarding schools is an educational institution that has a religious leader as a leader for the students both men and women. An institution of education boarding schools who want to create a religious and independent student, so that in teaching and educating values self-reliance in students, those in direct guided to perform daily activities independently without assistance others. This is done so that the soul of independence of students ingrained early on. Hope in the future when they mingle with society does not depend and can create jobs independently. But what distinguishes the Institute is led by a charismatic religious leader. Model of charismatic leadership is not only set on the characteristics of the outstanding trust, power and firm in conviction but there are spiritual depth factor aspects influenced in leading an institution and boarding schools.